Treatment Of Arowana Aquaculture Wastewater Using Sand, Activated Carbon And Zeolite In A Horizontal Prototype Model - Awalluddin, Nur Atiqah Ahmad (2019)
Arowana aquaculture industry have been blooming in Malaysia since 2008 and the production of the ornamental fish has contributed significantly towards the country economic growth. The most valuable Arowana species is the Golden Arowana which due to it intrinsic criteria can only breed successfully at Bukit Merah. This rises a concern towards water scarcity due to conjunctive uses between Arowana aquaculture industries with the Kerian rice growing area at Bukit Merah reservoir. Reusing and recycling the water from the Arowana Farm effluent could reduce the usage of water sources from the Bukit Merah reservoir. Therefore, a horizontal prototype model was established by incorporating sand, activated carbon (AC) and zeolite in treating ammoniacal nitrogen (NH3-N), total suspended solids (TSS), total phosphorus (TP) and iron (Fe (II)). A set of target removal was established for each of the pollutant through monitoring of water quality at the water intake and effluent of Arowana Farm. It was identified that the effluent need to achieved target removal for NH3-N, TSS, Fe (II) and TP of 62%, 73%, 35% and 33% respectively in order to have a better water quality as the water source intake. Batch study was performed to determine the performance of each adsorbent. The adsorption process in zeolite removed NH3-N with percentage of 86%. Adsorption of AC removed Fe (II) with 70% removal and adsorption of sand removed TP with percentage removal of 39%. Next, the optimum bed depth for each of the media was determined using Mixture Simplex Lattice design by Design Expert software. The optimum bed depth obtained for sand, AC and zeolite was in a ratio of 5cm: 5cm: 20cm respectively and was validated by employing column study experiment using an up flow flow-rate of 30ml/min. The optimum bed depth was then applied inside a horizontal prototype model. Horizontal prototype model experiment was conducted for 60 days (1440 hours). The targeted removal percentage with respect to the breakthrough time was obtained following the following sequence TSS<TP<Fe (II)<NH3-N with breakthrough time of 144 hours, 480 hours, 920 hours and 1200 hours respectively. These results show a good cooperation and capabilities among sand, AC and zeolite in treating Arowana aquaculture wastewater specifically for the removal of NH3-N, TSS, Fe (II) and TP.